2016
DOI: 10.1039/c5fo01060h
|View full text |Cite
|
Sign up to set email alerts
|

Food matrix and processing influence on carotenoid bioaccessibility and lipophilic antioxidant activity of fruit juice-based beverages

Abstract: The biological activity of carotenoids depends on their bioaccessibility and solubilization in the gastrointestinal tract. These compounds are poorly dispersed in the aqueous media of the digestive tract due to their lipophilic nature. Thus, it is important to analyze the extent to which some factors, such as the food matrix and food processing, may improve their bioaccessibility. Beverages formulated with a blend of fruit juices and water (WB), milk (MB) or soymilk (SB) were treated by high-intensity pulsed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 45 publications
2
42
0
2
Order By: Relevance
“…It is well known that the structure of the food matrix is one of the most important factors affecting the bioaccessibility of carotenoids. 21,34 In this regard, the results evidenced that PEFs would facilitate the release of carotenoid compounds from the tomato matrix. There are several studies that demonstrate that processing operation could disrupt cell walls and favour the release of carotenoids from the food matrix, thus leading to the enhancement of their bioaccessibility.…”
Section: Bioaccessibility Of Individual Carotenoids Of the Derived Prmentioning
confidence: 82%
See 1 more Smart Citation
“…It is well known that the structure of the food matrix is one of the most important factors affecting the bioaccessibility of carotenoids. 21,34 In this regard, the results evidenced that PEFs would facilitate the release of carotenoid compounds from the tomato matrix. There are several studies that demonstrate that processing operation could disrupt cell walls and favour the release of carotenoids from the food matrix, thus leading to the enhancement of their bioaccessibility.…”
Section: Bioaccessibility Of Individual Carotenoids Of the Derived Prmentioning
confidence: 82%
“…3,19,20 Since PEF treatments produce an electric breakdown of the cell membranes, it is thought that this technology could favour the release of carotenoids from the food matrix. In this regard, Rodríguez-Roque et al (2015) 21 reported that the application of high intensity PEF treatments enhanced the bioaccessibility of some carotenoids in fruitbased beverages. To the best of our knowledge, no information is available regarding the bioaccessibility of carotenoids in a processed plant-based food product as affected by the application of PEF treatments to intact raw fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The partly enhanced bioavailability of nutritious compounds, e.g. carotenoids, or the development of species-specific flavors have been shown to lead to an enhanced acceptability of processed NPs (Eriksen et al, 2016;Kinyuru et al, 2009;Reis et al, 2015;Rodriguez-Roque et al, 2016). However, cooking and other thermal processing have to be tailored to the NP properties to avoid loss in healthpromoting substances such as pro-vitamins A and C (Berni et al, 2015;Martinez-Hernandez et al, 2016;Rodriguez-Roque et al, 2015).…”
Section: Processingmentioning
confidence: 99%
“…Therefore, it is important to analyze how food matrix and processing affect their bioaccessibility. Rodriguez-Roque et al [15] formulated beverages with mixtures of fruit juices and water, milk, and soy applying three treatments: high intensity pulse electric fields, high pressure processing, and thermal treatment, to evaluate bioaccessibility of carotenoids and on lipophilic antioxidant activity. Bioaccessibility of carotenoids was reduced after all treatments, except for cis-violaxanthin and neoxanthin, which increased 79% in beverages treated with high intensity pulse electric fields and high pressure processing.…”
Section: Raw Plant Materials 21 Carotenoidsmentioning
confidence: 99%